2015
DOI: 10.1111/are.12938
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependence of cultured pearl grade and colour in the black-lipped pearl oysterPinctada margaritifera

Abstract: Pinctada margaritifera is an economically important marine bivalve species for cultured pearl production in French Polynesian aquaculture. In order to evaluate the influence of donor oyster age on pearl quality traits, experiments were conducted over 6 years using both grafts and surgreffe operations. At harvest, six pearl quality traits were recorded and compared: surface defects, lustre, grade, darkness level and visual colour. Analysing the quality traits of pearls harvested in the initial graft process and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…For overall cultured pearl grade, an archipelago signature appeared in favor of Gambier, where the highest rate of good quality pearls was found in comparison with Tuamotu and Society. This was in accordance with the significantly higher proportion of green pearls harvested in Gambier (+56% in comparison with other archipelagos) and evidence from previous studies demonstrating a positive correlation between this color and higher pearl grade (Ky et al 2014b), including for animals of the same age (Ky et al 2015f ). Pearl grade is based on the evaluation of surface defects and lustre.…”
Section: Discussionsupporting
confidence: 89%
“…For overall cultured pearl grade, an archipelago signature appeared in favor of Gambier, where the highest rate of good quality pearls was found in comparison with Tuamotu and Society. This was in accordance with the significantly higher proportion of green pearls harvested in Gambier (+56% in comparison with other archipelagos) and evidence from previous studies demonstrating a positive correlation between this color and higher pearl grade (Ky et al 2014b), including for animals of the same age (Ky et al 2015f ). Pearl grade is based on the evaluation of surface defects and lustre.…”
Section: Discussionsupporting
confidence: 89%
“…Recipient oysters might regulate the expression of biomineralization genes in the pearl sac and this could explain the weak difference between donor age categories for pearl sac expression levels. We confirmed results reported by Ky et al [ 31 ] where 2-year-old graft cells improved pearl grade, predominantly through a higher proportion of zero surface defects.…”
Section: Discussionsupporting
confidence: 92%
“…Despite existing knowledge about donor and recipient roles on pearl quality traits, only one previous study examined the effects that the age of donor oyster might have on pearl grade, lustre, surface defect and color. The study found that pearls produced from 2 year old donors were significantly better quality than those produced by 5 year old donors [ 31 ]. No study has examined the impact of using a younger donor oyster (< 2 years old) and the age effect on cultured pearl size.…”
Section: Introductionmentioning
confidence: 99%
“…A nacre deposition rate threshold may exist for a culture site, but also for the age of the donor oyster used as saibo, and age of the recipient oyster, as in the present experimental graft, where donors used in RRR site were younger than those used in the GMR site. Age influence on cultured pearl quality traits has been already examined in Ky et al, 2017c. In this last study, a duplicated graft experiment allowed the comparison of donor oyster families at 2 and 5 years old, where saibo (from middle mantle section) was inserted into recipient oysters aged 2.5 years old.…”
Section: Accepted Manuscriptmentioning
confidence: 99%